On the ozonolysis of unsaturated tosylhydrazones as a direct approach to diazocarbonyl compounds. Issue 16 (3rd April 2018) - Fegheh-Hassanpour, Younes; Ebrahim, Faisal; Arif, Tanzeel; Sintim, Herman O.; Claridge, Timothy D. W.; Amin, Nader T.; Hodgson, David M.
Abstract : Chemoselective alkene ozonolysis of unsaturated hydrazones then addition of Et3 N simultaneously reveals synthetically valuable carbonyl and ( via Bamford–Stevens) diazo functionality. Abstract : The scope and limitations are described of reacting unsaturated tosylhydrazones with O3 followed by Et3 N for the generation of 1, 4- and 1, 5-diazocarbonyl systems. Tosylhydrazones, from tosylhydrazide condensation with readily available δ- and ε-unsaturated α-ketoesters, led in the former case to a 2-pyrazoline whereas the latter cases led to α-diazo-ε-ketoesters, although a terminal alkene produced a tetrahydropyridazinol. Using the ozonolysis–Et3 N strategy, tosylhydrazones from cyclic enones give 2, 5- and 2, 6-diazoketones with aldehyde or ester functionality at the 1-position; the α-diazoaldehydes prefer the s- trans conformation, with a rotation barrier of 74 kJ mol −1 at 25 °C determined by NMR. This one-pot ozonolysis/Bamford–Stevens chemistry demonstrates both the tolerance of tosylhydrazones to ozone, and the subsequently added amine playing a dual role to directly transform the intermediate tosylhydrazone ozonides into products containing reactive diazo and ketone functionalities; such adducts are of particular value as precursors to cyclic carbonyl ylides for 1, 3-dipolar cycloadditions.